CT Multi- gamma source CT image reconstruction method and apparatus - CHANG, JI EUN; CHO, SEUNG RYONG; WI, SUN HEE; PARK, MI RAN (2017)
A multi-gamma source CT image reconstruction method and apparatus are disclosed. The method includes a step of irradiating a gamma ray to an empty space by a predetermined sequence of same gamma ray sources and obtaining the projected image of the empty space, a step of irradiating a subject simultaneously with gamma rays emitted from the same gamma ray sources, a step of estimating the projection image of the subject for each of the gamma ray sources by using the projection image of the obtained empty space, the projection image of the subject, and a basic reconstruction image, and a step of reconstructing the projected image of the estimated subject and generating a corrected reconstructed image. So, a beam hardening effect can be reduced. 다중 감마소스 CT 영상 재건 방법 및 장치가 개시된다. 복수개의 동일한 감마선원 중 하나의 감마선원씩 기 설정된 순서에 따라 감마선을 빈 공간에 조사하여 빈 공간의 투사영상을 얻는 단계, 복수개의 동일한 감마선원으로부터 방출되는 감마선을 동시에 피검체에 조사하여 피검체의 투사영상을 얻는 단계, 얻어진 빈 공간의 투사영상, 피검체의 투사영상 및 기초 재건영상을 이용하여 각각의 감마선원별로 피검체의 투사영상을 추정하는 단계 및 추정된 피검체의 투사영상을 재건하여 보정 재건영상을 생성하는 단계를 포함한다.